ANALISIS PENGEMBANGAN USAHA BISNIS BANK SAMPAH PADA USAHA MIKRO KECIL MENENGAH (STUDI KASUS PADA BANK SAMPAH DALANG COLLECTION DI PEKANBARU) - Yuliana "; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to analyze the Business Enterprise Development Bank Trash On Micro small medium (case studies On Waste Bank Mastermind Collection at Pekanbaru). In the Business Development Bank Trash Mastermind Collection, has undergone various changes the pattern of business development. Changes in the pattern of business development is done because some of the efforts the mastermind Collection not previously in accordance with the long-term business needs. Source data obtained directly from the key informant interview process to get accurate information.In determining the subject will be examined, researchers using a purposive sampling technique. Purposive sampling technique of sampling means intentionally. That is, the researcher determines its own samples taken since there are certain considerations. So, the sample taken randomly, but not determined by researchers. The method in this research is descriptive analysis that describes an overview of research on the variable, and then accompanied by a decipherment based on research results, data reduction stage, the presentation of data, as well as the withdrawal of the conclusion to further sharpen the writing of the results of this research.The study concluded that development of the mastermind collection focused on the renewal of the product. Where every product will be tailored to the needs of consumers. To support the development of long-term, Puppeteer also collaborated with various agencies concerned. The cooperation efforts rated as one of the driving factors are very good for the development of the mastermind Collection. The driving factors of business development the mastermind collection lies in the participation of the community and the availability of raw materials, as well as government support. Still the existence of public participation provide a positive influence for the continuation of the process of recycling the garbage container. Factors that hinder the development of the mastermind collection lies in the limitation of production time, awareness of the environment and mission of the mastermind collection of low as well as the commitment of the workers is very low.Keywords: Product, Human Resources, Network Marketing